Comparative Study of Video Compression Techniques- H.264/AVC - Bhagwat, Priyanka (International Journal of Computer Sciences and Engineering, 2025)
This paper reviews several recently information hiding technique in H.264/avc video compression standards. H.264/AVC is a recently concluded video compression standard jointly developed by ITU-T and ISO MPEG standards committees. The standard is becoming more favoured as it promises much higher compression than that possible with earlier standards. The objective of the H.264/AVC project was to create a standard, capable of providing good video quality at substantially lower bit rates than foregoing standards (i.e., half or less the bit rate of MPEG-2, H.263, or MPEG-4 Part 2), without increasing the difficulty of design. This paper provides an overview of the H.264 features and summarizes the emerging studies associated to new coding features of the standard. H.264 entails significant improvements in coding efficiency, latency, difficulty and robustness. It provides new possibilities for creating better video encoders and decoders that provide higher quality video streams at prolonged bit-rates (compared to previous standards), or, conversely, the same quality video at a lower bit-rate. Hence, suitable video compression techniques that meet video applications requirements have to be selected.